Media Ethics and Legal Accountability in the Digital Age - Uzma Abbas (Journal of Advanced Research in Journalism & Mass Communication, 2025)
The digital revolution has transformed journalism into a fast,networked, and interactive ecosystem where information travels globally within seconds. While this transformation has expanded access and participation, it has also introduced profound ethical and legal challenges. This paper explores the evolving landscape of media ethics and legal accountability in the digital age, focusing on misinformation, privacy, copyright violations, and the ethical use of user-generated content. It analyzes the role of regulatory frameworks such as the Information Technology Act (India), GDPR (Europe), and global press codes in defining responsible journalism. The discussion highlights how professional ethics must adapt to algorithmic amplification, influencer culture, and real-time citizen journalism. It concludes by proposing strategies for reinforcing media accountability through digital literacy, newsroom training, transparent self-regulation, and collaborative fact-checking.